Pemanfaatan Citra Satelit Untuk Mengidentifikasi Perubahan Bentang Lahan - Shaliha Reghina Ratna Amalia; Jihan Dhiya Ulhaq; Maharani Putri; Salwa Dhia Tisani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study explores the use of satellite imagery in identifying and monitoring landscape change in the context of sustainable development and natural resource management. The research method used is literature study, by collecting, reviewing and analyzing various sources of information relevant to the research topic. The results of the analysis show that satellite imagery, especially from the Landsat satellite, plays an important role in mapping land use changes over a long period of time, which is useful for monitoring and analyzing land change. Various techniques and methods, such as manual digitization, use of GIS, and guided classification methods, are used to identify landscape changes. Factors such as sensor technology, image processing, ground truth data, and the complexity of the study environment influence the precision and accuracy of analysis results. The conclusion of this study is that the use of satellite imagery in managing and monitoring landscape change provides significant benefits in the context of sustainable development, but also requires a long-term and inclusive approach to ensure the use of this technology can take place effectively and sustainably.